Identifying Genomic Expression at Single-Cell Level or a Small Number of Cells: A Review - Biaoru Li (Innovations in Microbiology and Biotechnology Vol. 8, 2022)
Recent breakthroughs in functional genomics allow us to assess the expression of thousands of genes in the mammalian genome. Parallel gene expression has been extensively analysed and screened using methods including microarrays, expressed tag sequencing (EST), serial analysis of gene expression (SAGE), subtractive cloning and differential display (DD), and two-dimensional electrophoresis gel. The limits of these functional genomic approaches are challenged by some pathological processes, such as carcinogenesis and solid tumour growth, where the former results from a single-cell difficulty and the latter from a mixed-cell issue. To completely comprehend the roles of cells in carcinogenesis or in heterogeneous solid tumour masses, scientists and physicians must devise a mechanism for identifying genomic expression profiles for a single cell or a small number of cells. This article examines recently created techniques that allow single-cell or multiple-cell functional genomic analysis. The paper will also discuss various methods for single-cell genomic expression at the DNA, mRNA, protein, and post-translational modification levels.